The association between international and domestic air traffic and the coronavirus (COVID-19) outbreak - Lau, Hien; Khosrawipour, Veria; Kocbach, Piotr; Mikolajczyk, Agata; Ichii, Hirohito; Zacharski, Maciej; Bania, Jacek; Khosrawipour, Tanja (Journal of microbiology, immunology and infection, 2020)
The World Health Organization (WHO) has declared the current outbreak of the novel coronavirus (COVID-19) a global pandemic. Many countries are facing increasing numbers of COVID-19 cases, which are, in their origin mostly attributed to regular international flight connections with China. This study aims to investigate this relation by analyzing available data on air traffic volume and the spread of COVID-19 cases. and findings: We analyzed available data on current domestic and international passenger volume and flight routes and compared these to the distribution of domestic and international COVID-19 cases. Our data indicate a strong linear correlation between domestic COVID-19 cases and passenger volume for regions within China (r2 = 0.92, p = 0.19) and a significant correlation between international COVID-19 cases and passenger volume (r2 = 0.98, p < 0.01). The number of flight routes as well as total passenger volume are highly relevant risk factors for the spread of current COVID-19. Multiple regions within Asia, as well as some in North America and Europe are at serious risk of constant exposure to COVID-19 from China and other highly infected countries. Risk for COVID-19 exposure remains relatively low in South America and Africa. If adequate measures are taken, including on-site disease detection and temporary passenger quarantine, limited but not terminated air traffic can be a feasible option to prevent a long-term crisis. Reasonable risk calculations and case evaluations per passenger volume are crucial aspects which must be considered when reducing international flights.